An ethnobotanical survey of medicinal plants focusing on cardiovascular diseases used by the local people in and around Dinajpur district, Bangladesh (Journal of the Asiatic Society of Bangladesh, Science, 2023)
This study aimed to document the medicinal plants through semi-structured interviews, key informant discussions, and informal conversations with local people in and around the Dinajpur district, Bangladesh. A total of 109 medicinal plant species distributed in 60 families with 210 formularies to treat 55 ailments were recorded. The most frequently utilized plant populations were herbs, followed by trees, shrubs, and climbers. Oral consumption was the main mode of treatment in the study area and was followed by external application. The highest factor of informant consensus (Fic) values was found in heart disease, followed by diabetes, gastrointestinal disorders, skin disease, respiratory disorders, sexual disease, and cuts and wounds. In the present survey, eight species have attained a fidelity level of 100 percent (Fl). Among the plants, 25 species have been used to treat cardiovascular diseases. The most cited medicinal plants for cardiac management are Terminalia arjuna (Roxb. ex DC.) Wight & Arn., Baccaurea ramiflora Lour., Dillenia indica L., Allium sativum L., Tamarindus indica L., Rauvolfia serpentina (L.) Benth. ex Kurz., Terminalia chebula Retz., Phyllanthus emblica L., Averrhoa carambola L. and Spondias pinnata (L. f.) Kurz. The ethnobotanical uses of the documented plants provide basic data, and further investigation focusing on pharmacological research is essential to confirm the results. Numerous threats to medicinal plants were identified during the ethnobotanical survey in the study area. Some recommendations are provided to mitigate the threats and the conservation of medicinal plants.J. Asiat. Soc. Bangladesh, Sci. 48(1-2): 19-40, June-December 2022